The comrade of Vaclovas Biržiška - Izidorius Kisinas - Žiedūnė Zaveckienė (Knygotyra)
In this article, the lesser-known periods of L. Kisinas's life and activities connected with V. Biržiška are revealed. From 1935 to 1941, L. Kisinas worked in the libraries of Kaunas and Vilnius University, both headed by V. Biržiška. During that time, L. Kisinas prepared many bibliographical works such as "Professor Eduardas Volteris's Bibliography" (1928), "Professor Mykolas Biržiška's Bibliography" (1931), "Antanas Smetona's Bibliography and Biobibliography" (1935), and others.